Implementation of the Application of Khiyar in Buying and Selling Transactions in Traditional Markets and Buying and Selling Online - Nurli Azma; Rong Shi Shu; Bell Juanes (Yayasan Adra Karima Hubbi, 2023)
Basically, when conducting a sale and purchase transaction, the party concerned has the right to continue or cancel the contract. This is a solution for Islam in order to create convenience for consumers to make buying and selling transactions, namely with the existence of khiyar rights. Khiyar is needed in a sale and purchase transaction so that the parties concerned can maintain the interests of their needs and create willingness on both sides so that they cannot cause losses. What happens most often is in online buying and selling transactions because at that time the parties did not meet face to face. The purpose of this writing is to explain and inform anyone who conducts buying and selling transactions both in traditional markets and buying and selling online that how important it is to apply khiyar in buying and selling so as not to cause losses. The method used in this writing is by interviewing the parties who have canceled the sale and purchase contract. The result of this writing is that it can be seen how many parties feel a loss in a transaction because many sellers are dishonest or do not know about the damage to the goods they sell. This happens a lot in traditional markets which causes buyers to feel at a loss when they buy it. Besides that, there are several traditional markets that can apply khiyar rights to consumers, but very few do this, because the sellers are afraid of feeling a loss if consumers return goods that have been damaged and then replace them with other goods. Especially in buying and selling online, many sellers who apply the system do not accept cancellation of sales and purchases if the item has been received by the consumer.